2011
DOI: 10.1007/s12570-011-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of open reduction and internal fixation of isolated posterior cruciate ligament avulsion fracture

Abstract: Purpose Although posterior cruciate ligament avulsion fracture is a rare condition, but lack of its treatment results in knee instability. Identification of functional and clinical outcomes after open reduction and internal fixation was the main goal of this research. Methods Thirty-one patients, underwent operation due to isolated tibial posterior cruciate ligament avulsion fracture, were followed-up for a mean of 24 months (range 13-44 months). Outcome was evaluated by International Knee Documentation Commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…By considering these factors in future studies, the error probability can be minimised. The Lysholm knee score in the present study was not significantly different from other studies [11], [13], [15], [16], and most patients achieved a good and acceptable score after the surgery. The patients in this study had no problem with knee joint instability and disabling functional disorder compared to their normal knee.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…By considering these factors in future studies, the error probability can be minimised. The Lysholm knee score in the present study was not significantly different from other studies [11], [13], [15], [16], and most patients achieved a good and acceptable score after the surgery. The patients in this study had no problem with knee joint instability and disabling functional disorder compared to their normal knee.…”
Section: Discussioncontrasting
confidence: 86%
“…Positive posterior drawer test and the results of the questionnaire (relatively good and close to normal) were one of the considerable issues in this study and other similar studies, such as the study by Rezazadeh et al, [15] or Sergio Rocha et al, in Brazil [11]. Such results were not expected by assuming that the present study investigated the posterior cruciate ligament avulsion considering the preliminary design of the study.…”
Section: Discussionmentioning
confidence: 44%
“…Eight studies reported scores via the IKDC. 4,9,10,19,20,28-30 A total of 182 knees were treated surgically, of which the IKDC reported 65.9% as normal or grade A, 29.1% as nearly normal or grade B, and 10.4% as abnormal or grade C. Two studies reported on the Tegner activity score. 30,31 Sabat et al 30 reported a mean preinjury Tegner score as 7.1, compared with a mean postinjury score of 6.8.…”
Section: Resultsmentioning
confidence: 99%
“…¶ Postoperative stiffness owing to arthrofibrosis was a documented complication in a total of 8 patients dispersed in 5 of the 20 studies. 4,20,26,29,40 In 5 of the 8 patients, postoperative immobilization was maintained for ≥3 weeks. All 8 patients underwent manipulation under anesthesia for this complication.…”
Section: Resultsmentioning
confidence: 99%
“…The posterior cruciate ligament (PCL) is the stronger of the 2 cruciate ligaments of the knee and has a major role in stabilizing the knee joint 1, 2. Functionally, the PCL is a primary restraint to posterior tibial translation at all flexion angles and also for internal rotation beyond 90° of flexion 3 .…”
mentioning
confidence: 99%